Inventarisasi Tumbuhan Liar Berpotensi Obat Pada Kawasan Desa Kanigoro Kabupaten Malang - Nafi’ah, Ilmatun; Diyah Ayu Widyaningrum; Hindun, Nurmala (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Kanigoro Village is located in Malang Regency. It is home to a variety of plants with medicinal potential. However, not many residents, especially the younger generation, are familiar with the traditional knowledge surrounding these plants. An inventory of the village's plants could be used to preserve traditional knowledge and local biodiversity. The purpose of this research is to preserve medicinal plants in the Kanigoro Village area of ??Malang Regency through an inventory. The study was conducted using a descriptive-exploratory method through interviews with local knowledgeable community members and field observations in June 2025. The research findings identified 20 species of medicinal plants from 16 families commonly utilized by the community, such as Pluchea indica, Stachytarpheta jamaicensis, Hippobroma longiflora, Clitoria ternatea, Paederia foetida, Phyllanthus niruri, Portulaca oleracea, Amaranthus viridis, and others. There are 20 species from 16 plant families used and processed as traditional medicine, with the most common medicinal plants belonging to the Fabaceae, Rubiaceae, Zingiberaceae, and Asteraceae families. There are 90 types of diseases that can be treated using wild plants found in Kanigoro village. The plants are most commonly found in yard habitats. This research emphasizes the importance of conserving wild plants and preserving ethnobotanical knowledge, serving as a basis for the development of traditional medicines and environmental education. The data obtained are expected to be beneficial for further research and the development of herbal products based on local plants.